2023
DOI: 10.1002/mabi.202300149
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of Human Mesenchymal Stem Cells on Conductive Substrates Promotes Neural Priming

Abstract: Electrical stimulation (ES) within a conductive scaffold is potentially beneficial in encouraging the differentiation of stem cells toward a neuronal phenotype. To improve stem cell‐based regenerative therapies, it is essential to use electroconductive scaffolds with appropriate stiffnesses to regulate the amount and location of ES delivery. Herein, biodegradable electroconductive substrates with different stiffnesses are fabricated from chitosan‐grafted‐polyaniline (CS‐g‐PANI) copolymers. Human mesenchymal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 93 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Several studies have demonstrated that neuronal differentiation, both of MSCs and NSCs, can be achieved by electrical stimulation [5,[28][29][30]; as well as it is possible to influence the neural lineage of differentiated NSCs through the electrical stimulation [7]. Responsible for the response to electrical stimulation are the voltage-gated calcium channels [29,31].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that neuronal differentiation, both of MSCs and NSCs, can be achieved by electrical stimulation [5,[28][29][30]; as well as it is possible to influence the neural lineage of differentiated NSCs through the electrical stimulation [7]. Responsible for the response to electrical stimulation are the voltage-gated calcium channels [29,31].…”
Section: Discussionmentioning
confidence: 99%
“…Electrical stimulation protocol conditions MSCs to enhance their proliferation, migration, differentiation, and scaffold adherence[ 20 ]. The effect of physiological level electrical stimulation has been shown to impact slowly; three days of culture has little effect compared to seven days and fourteen days to stimulate osteogenic, chondrogenic, and neural differentiation of the MSCs[ 21 , 22 ]. Similarly, the impact of electric stimulation is also determined by whether it is continuous or pulsed.…”
Section: Pretreatment Approaches Of Mscsmentioning
confidence: 99%